Impact of ß-Glucan with Non-Glucan Biomaterials on Growth Performance, Carcass Characteristics, and Viable Count of Lactobacilli in Broiler Chicks - Hashaam, H. M.; Naveed, S.; Rehman, S.; Zeeshan, M.; Rahman, A.; Lokapirnasari, W. P.; Hussain, M. A.; Begum, R.; Jamal, M.; Yulianto, A. B. (Faculty of Animal Science, IPB University, 2024)
Probiotics, prebiotics, and immunomodulators like β-glucan have become popular feed additives. Thus, this study examined the effects of a β-glucan product fortified with dietary biomaterials (fats, proteins, and minerals) on broiler chicks’ growth, carcass features, immunological response, white blood cell (WBC) count, and viable count (number of living cells) of lactobacilli. Day-old Ross-308 (n=250) were randomly assigned to 1 of 5 dietary treatments; A= basal diet, B= basal diet + 40 mg/kg of avilamycin, C= basal diet + 250 g/ton β-glucan product, D= basal diet + 500 g/ton β-glucan product, and E= basal diet + 750 g/ton β-glucan product. The starter diet was administered from days 1 to 14, the grower diet from days 15 to 21, and the finisher diet from days 22 to 35. Each treatment had 5 repetitions of 10 birds. On days 7 and 20, all birds were eye-drop inoculated against the Newcastle disease (ND) vaccine. Three chickens from each replication of all treatments were slaughtered on day 35 to examine carcass features and collect ileal digesta. White blood cell and viable lactobacilli counts at the end of the trial showed the effect of β-glucan supplementation. Throughout the trial, β-glucan administration did not increase average daily weight gain. The treatments did not change WBC or viable count; however, lactobacilli count increased (p≤0.05) in treatment group E. Treatment E increased (p≤0.05) ND-vaccination antibody-titers but did not affect immunological organ development. Treatment diet E (base diet +750 mg/t β-glucan product) improved broiler immunity and gut microbiota. In conclusion, the addition of β-glucan to broiler feed enhanced the beneficial gut flora, particularly Lactobacilli and immune response, and may serve as an alternative to antibiotics.